2018
DOI: 10.33225/pec/18.76.864
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Loading Due to Self-Directed Learning, Complex Questions and Tasks in the Zone of Proximal Development of Students

Abstract: The aim of the research was to explore the levels of cognitive loading induced by certain tenets of constructivist pedagogy namely self-directed learning complex questions and zone of proximal development. The study also sought to investigate the associations between these constructs and with cognitive loading and complex questions. Data for the research were collected using a questionnaire survey of a sample of students studying towards undergraduate degrees in construction-related studies at - public univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, one construct fell below this threshold. AVE values of less than 0.50 but greater than 0.40 are also considered acceptable when other measures of validity and reliability are satisfactory because AVE is often too strict, and CR alone can be used to assess reliability (Malhotra and Dash, 2011; Zulu et al , 2018). Therefore, the scales for the study are reliable.…”
Section: Resultsmentioning
confidence: 99%
“…However, one construct fell below this threshold. AVE values of less than 0.50 but greater than 0.40 are also considered acceptable when other measures of validity and reliability are satisfactory because AVE is often too strict, and CR alone can be used to assess reliability (Malhotra and Dash, 2011; Zulu et al , 2018). Therefore, the scales for the study are reliable.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is not surprising that students perceive anatomy learning as centered on imbibing and regurgitating knowledge. These observations may reflect that these students are aware and control their learning to prevent cognitive overloading in the face of heavy and complex content (Zulu et al, 2018). Many studies have left out this section of the ASSIST (Entwistle et al, 2013), however, in the present study, it has shed some light on how students view anatomy learning, especially when many studies have suggested promoting deeper approaches to learning ahead of the surface apathetic ones (Hawk and Shah, 2007; Feeley and Biggerstaff, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the utility of study skills should go beyond matching them with a specific type of tuition. For instance, when medical students are aware of their study habits, study skills and preferences they inadvertently reflect on their cognitive, metacognitive (Khine et al, 2019), and working memory enhancement abilities (Zulu et al, 2018). Thus, medical students will pay attention to how they organize self-regulated and reflective behaviors than merely being vessels awaiting the best matching teaching tools from anatomy instructors.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolding can lead students to learn more directed and can overcome learning disorientation and cognitive load they experience (Kalyuga, 2009;Hsieh, Lee, & Su, 2013), especially when they are not under teacher control or do independent learning (Butz, Stupnisky, & Pekrun, 2015). Although other findings reveal that the cognitive load experienced by students is also caused by the complexity of the questions and tasks given by the teacher or lecturer to students (Zulu, Haupt, & Tramontin, 2018).…”
mentioning
confidence: 99%